2016
DOI: 10.1128/aac.01747-15
|View full text |Cite
|
Sign up to set email alerts
|

Mutant Alleles of lptD Increase the Permeability of Pseudomonas aeruginosa and Define Determinants of Intrinsic Resistance to Antibiotics

Abstract: bGram-negative bacteria provide a particular challenge to antibacterial drug discovery due to their cell envelope structure. Compound entry is impeded by the lipopolysaccharide (LPS) of the outer membrane (OM), and those molecules that overcome this barrier are often expelled by multidrug efflux pumps. Understanding how efflux and permeability affect the ability of a compound to reach its target is paramount to translating in vitro biochemical potency to cellular bioactivity. Herein, a suite of Pseudomonas aer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
43
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 100 publications
4
43
0
Order By: Relevance
“…The strain P. aeruginosa Z61 has the full complement of the genes necessary for induction of β-lactamases, but it expresses a mutant version of the β-lactamase with diminished activity. [22] Nonetheless, using the nitrocefin assay we observed a 4.7 fold increase of induction of β-lactamase at quarter-MIC level of cefoxitin. The same experiment performed with the bacteria exposed to 100 μg/mL muropeptides 2e or 4e resulted in 1.4 or 1.7 induction, respectively (Table S1).…”
mentioning
confidence: 94%
“…The strain P. aeruginosa Z61 has the full complement of the genes necessary for induction of β-lactamases, but it expresses a mutant version of the β-lactamase with diminished activity. [22] Nonetheless, using the nitrocefin assay we observed a 4.7 fold increase of induction of β-lactamase at quarter-MIC level of cefoxitin. The same experiment performed with the bacteria exposed to 100 μg/mL muropeptides 2e or 4e resulted in 1.4 or 1.7 induction, respectively (Table S1).…”
mentioning
confidence: 94%
“…However, enzymes capable of inactivating drugs are only one factor contributing to intrinsic drug resistance in bacteria. Other factors including membrane penetration, efflux mechanisms, and endogenous native substrate competition contribute to intrinsic drug resistance262728. The ability to improve susceptibility of M .…”
Section: Discussionmentioning
confidence: 99%
“…The OMP LptD, formerly known as OstA or Imp, has been subjected to in-depth investigation in E. coli (see reviews of refs 28 and 43), and it has also been subjected to studies in several other Gram-negative bacteria, such as Neisseria gonorrhoeae 36, Acinetobacter baumannii 26, N. meningitidis 44 and Pseudomonas aeruginosa 45, in recent years. In these studies, LptD was revealed to be one a component of the LPS transport complex, which consists of 7 essential proteins (LptA-LptG), and its physiological function has been suggested to mediate the final translocation of fully synthesized LPS to the cell surface, thus being involved in cell envelope biogenesis46.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, the LPS that surrounds bacteria forms a permeation barrier, which prevents hydrophobic antibiotics from entering the cells, thus conferring antibiotic resistance252854. It has been shown previously that deletion of lptD caused a significant decrease in cell LPS253645, and the lack of LPS is commonly accompanied by a decreasing growth rate and increasing sensitivity to antibiotics26455556. The LPS transport proteins have accordingly been considered attractive targets for new drug development5758.…”
Section: Discussionmentioning
confidence: 99%